Comparative Study of Regulatory T Cell Function of Human CD25+CD4+ T Cells from Thymocytes, Cord Blood, and Adult Peripheral Blood - Wakae Fujimaki; Nozomu Takahashi; Kei Ohnuma; Masayoshi Nagatsu; Hiromi Kurosawa; Satoko Yoshida; Nam H. Dang; Takehiko Uchiyama; Chikao Morimoto (Clinical and Developmental Immunology)
CD25+CD4+ regulatory T cells suppress T cell activation and regulate multiple immune reactions in in vitro and in vivo studies. To define the regulatory function of human CD25+CD4+ T cells at various stages of maturity, we investigated in detail the functional differences of CD25+CD4+ T cells from thymocytes, cord blood (CB), and adult peripheral blood (APB). CB CD25+CD4+ T cells displayed low-FOXP3 protein expression level and had no suppressive activity. In contrast, CD25+CD4+ T cells from thymocytes or APB expressed high expression level of FOXP3 protein associated with significant suppressive activity. Although CB CD25+CD4+ T cells exhibited no suppressive activity, striking suppressive activity was observed following expansion in culture associated with increased FOXP3 expression and a shift from the CD45RA+ to the CD45RA− phenotype. These functional differences in CD25+CD4+ T cells from Thy, CB, and APB hence suggest a pathway of maturation for Treg in the peripheral immune system.